A Comparison of Methods Used for the Calibration of Radiocarbon Dates. Issue 3 (18th July 2016) - Aitchison, T C; Leese, Morven; Michczynska, D J; Mook, W G; Otlet, R L; Ottaway, B S; Pazdur, M F; Van Der Plicht, J; Reimer, P J; Robinson, S W; Scott, E M; Stuiver, Minze; et al.
Abstract : Current calibration methods for single and replicate 14 C dates are compared. Various forms of tabular and graphic output are discussed. Results from all the methods show reasonable agreement but further methodological development and improvements in computer output are required. Comparison of existing techniques for a series of non-contemporaneous dates showed less agreement amongst participants on this issue. We recommend that calibrated dates should be presented as a combination of graphs and ranges, in preference to mean and standard deviation.